Given the differential equation
"(x-y)p+(y-x-z)q=z"Consider a quasilinear equation
"a(x,y,z)p+b(x,y,z)q=c(x,y,z)"
By Lagrange’s method the auxiliary equations are as following:
"\\frac{dx}{a(x,y,z)}=\\frac{dy}{b(x,y,z)}=\\frac{dz}{c(x,y,z)}"
So, for the given quasilinear equation we come to the system in the symmetric form
"\\frac{dx}{(x-y)}=\\frac{dy}{y-(x+z)}=\\frac{dz}{z}"One of a way to solve the system in symmetric form is to use the equal fractions property
"\\frac{a_1}{b_1}=\\frac{a_2}{b_2}=\\frac{a_3}{b_3}=\\ldots=\\frac{\\lambda_1a_1+\\lambda_2a_2+\\cdots+\\lambda_na_n}{\\lambda_1b_1+\\lambda_2b_2+\\cdots+\\lambda_nb_n}"In our case, Choosing "\\lambda_1=\\lambda_2=\\lambda_3=1" as multipliers, each fraction on
"\\frac{dx}{(x-y)}=\\frac{dy}{y-(x+z)}=\\frac{dz}{z}=\\frac{1\\cdot dx+1\\cdot dy+1\\cdot dz}{1\\cdot(x-y)+1\\cdot(y-x-z)+z}\\\\[0.3cm]\n\\frac{dx}{(x-y)}=\\frac{dy}{y-(x+z)}=\\frac{dz}{z}=\\frac{dx+dy+dz}{0}\\longrightarrow\\\\[0.3cm]\nd(x+y+z)=0\\longrightarrow\\boxed{x+y+z=C_1}"
Take the last two fractions of the auxiliary equation and using "x+y+z=C_1" we get
"\\left\\{\\begin{array}{l}\n\\displaystyle\\frac{dy}{y-(x+z)}=\\displaystyle\\frac{dz}{z}\\\\[0.3cm]\nx+y+z=C_1\n\\end{array}\\right.\\longrightarrow\\left\\{\\begin{array}{l}\n\\displaystyle\\frac{dy}{y-(C_1-y)}=\\displaystyle\\frac{dz}{z}\\\\[0.3cm]\n(x+z)=C_1-y\n\\end{array}\\right.\\\\[0.3cm]\n\\int\\frac{dy}{2y-C_1}=\\int\\frac{dz}{z}\\longrightarrow\\\\[0.3cm]\n\\frac{\\ln|2y-C_1|}{2}=\\ln|z|+\\ln|C_2|\\longrightarrow\\ln|2y-C_1|-2\\ln|z|=2\\ln|C_2|\\\\[0.3cm]\n\\ln\\left|\\frac{2y-C_1}{z^2}\\right|=\\ln|\\underbrace{C_2^2}_{C_3}|\\longrightarrow\\frac{2y-(x+y+z)}{z^2}=C_3\\\\[0.3cm]\n\\boxed{\\frac{y-x-z}{z^2}=C_3}"We have found two integrals for the given equation
"\\left\\{\\begin{array}{l}\nx+y+z=C_1\\\\[0.3cm]\n\\displaystyle\\frac{y-x-z}{z^2}=C_3\n\\end{array}\\right."Therefore, any integral surface of the differential equation "(\ud835\udc65\u2212\ud835\udc66)\ud835\udc5d+(\ud835\udc66\u2212\ud835\udc65\u2212\ud835\udc67)\ud835\udc5e=\ud835\udc67" is described by the equation
"\\varphi\\left(C_1,C_3\\right)=0\\longrightarrow\\\\[0.3cm]\n\\boxed{\\varphi\\left((x+y+z),\\frac{y-x-z}{z^2}\\right)=0\\,\\text{is the general integral}}"where "\\varphi" is an arbitrary smooth function.
Particular solution:
A particular solution through the circle "z=1, x^2+y^2=1"
"\\left\\{\\begin{array}{l}\nx+y+z=C_1\\\\[0.3cm]\n\\displaystyle\\frac{y-x-z}{z^2}=C_3\\\\[0.3cm]\nz=1\\\\[0.3cm]\nx^2+y^2=1\n\\end{array}\\right.\\longrightarrow\n\\left\\{\\begin{array}{l}\nx+y+1=C_1\\\\[0.3cm]\ny-x-1=C_3\n\\end{array}\\right.\\\\[0.3cm]\n\\left\\{\\begin{array}{l}\nx+y+1=C_1\\\\[0.3cm]\ny-x-1=C_3\n\\end{array}\\right.\\longrightarrow\\left\\{\\begin{array}{l}\ny=\\displaystyle\\frac{C_1+C_3}{2}\\\\[0.3cm]\nx=\\displaystyle\\frac{C_1-C_3}{2}-1\n\\end{array}\\right.\\\\[0.3cm]"
Substituting the found expressions into the second condition
"x^2+y^2=1\\longrightarrow\\left(\\frac{C_1-C_3}{2}-1\\right)^2+\\left(\\frac{C_1+C_3}{2}\\right)^2=1\\\\[0.4cm]\n\\frac{C_1^2-2C_1C_3+C_3^2}{4}-(C_1-C_3)+1+\\frac{C_1^2+2C_1C_3+C_3^2}{4}=1\\\\[0.4cm]\n\\frac{2C_1^2+2C_3^2}{4}-C_1+C_3=0\\\\[0.4cm]\nC_1^2+C_3^2-2C_1+2C_3=0\\\\[0.4cm]\n\\boxed{C_1(C_1-2)+C_3(C_3+2)=0}"Since, "\\varphi(C_1,C_3)=0" , so
"\\varphi(C_1,C_3)=C_1(C_1-2)+C_3(C_3+2)-\\text{Particular solution}"
Conclusion,
"\\left\\{\\begin{array}{l}\nx+y+z=C_1\\\\[0.3cm]\n\\displaystyle\\frac{y-x-z}{z^2}=C_3\n\\end{array}\\right.\\longrightarrow\\\\[0.3cm]\n(x+y+z)(x+y+z-2)+\\frac{y-x-z}{z^2}\\cdot\\left(\\frac{y-x-z}{z^2}+2\\right)=0\\\\[0.3cm]"ANSWER
"\\varphi\\left((x+y+z),\\frac{y-x-z}{z^2}\\right)=0\\,\\text{is the general solution}\\\\[0.3cm]\n\\text{Particular solution is}\\\\[0.3cm]\n(x+y+z)(x+y+z-2)+\\frac{y-x-z}{z^2}\\cdot\\left(\\frac{y-x-z}{z^2}+2\\right)=0"
Comments
Leave a comment